2019
DOI: 10.1136/bmjopen-2018-028753
|View full text |Cite
|
Sign up to set email alerts
|

Winter cancellations of elective surgical procedures in the UK: a questionnaire survey of patients on the economic and psychological impact

Abstract: ObjectivesTo quantify the economic and psychological impact of the cancellation of operations due to winter pressures on patients, their families and the economy.DesignThis questionnaire study was designed with the help of patient groups. Data were collected on the economic and financial burden of cancellations. Emotions were also quantified on a 5-point Likert scale.SettingFive NHS Hospital Trusts in the East Midlands region of England.ParticipantsWe identified 796 participants who had their elective operatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 13 publications
1
54
0
2
Order By: Relevance
“… 25 , 26 More recently, a study examining nearly 400 patients who experienced a surgical cancellation revealed that over 30% reported extreme emotional impacts (e.g., extreme sadness, stress, anger) and nearly 60% reported moderate concern about their deteriorating health condition as a result of the cancellation. 27 The lower value from the current study may reflect the fact that the majority of patients eventually underwent surgery, meaning the adverse impacts of their surgical cancellations/postponements may have been less salient at the time of the survey.…”
Section: Discussionmentioning
confidence: 82%
“… 25 , 26 More recently, a study examining nearly 400 patients who experienced a surgical cancellation revealed that over 30% reported extreme emotional impacts (e.g., extreme sadness, stress, anger) and nearly 60% reported moderate concern about their deteriorating health condition as a result of the cancellation. 27 The lower value from the current study may reflect the fact that the majority of patients eventually underwent surgery, meaning the adverse impacts of their surgical cancellations/postponements may have been less salient at the time of the survey.…”
Section: Discussionmentioning
confidence: 82%
“…There is no existing knowledge as to what impact this loss of surgical capacity will have on patients' surgical condition and associated health, or in terms of well‐being, functional capacity, risk of loss of function or adverse effects on prognosis. It is known from cancellations under normal circumstances that patients can experience feelings of sadness, disappointment, anger, frustration and stress. This comes in addition to the potential economic consequence (loss of work, sick leave or inability to maintain occupancy) and impact on family life.…”
Section: Preparing Surgical Services For Postpandemic Phasementioning
confidence: 99%
“…This has a significant impact, both on the capacity of the surgical system as well as at a personal level, causing extreme stress and anxiety for patients. One study showed that 30% of patients who had operations cancelled during winter pressures complained of extreme stress and frustration as well as 59% reporting moderate or severe concern about a deterioration in their condition [104], in addition to the impact on a patient's family as well.…”
Section: Recovery Of Surgical Servicesmentioning
confidence: 99%